Ecological niche modelling of species of the rose gall wasp Diplolepis (Hymenoptera: Cynipidae) on the Iberian Peninsula - Sara SARDÓN-GUTIÉRREZ (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Diplolepis (Hymenoptera: Cynipidae) are gall wasps that induce conspicuous galls on Rosa spp. (Rosaceae). These species are distributed globally and in Europe some are especially common and are founder organisms of biological communities composed of different insects. However, the ecological niches of these species have not been studied in detail. We modelled the potential distributions of these species using the locations of the galls of the four most abundant species of Diplolepis on the Iberian Peninsula (Diplolepis mayri, Diplolepis rosae, Diplolepis eglanteriae and Diplolepis nervosa, the galls of latter two are indistinguishable) using four different algorithms and identified the resulting consensus for the species. We compared the potential distributions of these species, considering their spatial complementarity and the distributions of their host plants. We found that D. mayri and D. eglanteriae/nervosa have complementary distributions on the Iberian Peninsula. The former species is found in the Mediterranean region, while D. eglanteriae and D. nervosa are distributed mainly in the Eurosiberian region. Diplolepis rosae has the widest distribution on the Iberian Peninsula. Our models constitute the first effort to identify suitable areas for species of Diplolepis species on the Iberian Peninsula and could be useful for understanding the evolutionary ecology of these species throughout their distribution in the western Palearctic.